Is gene doping going to change the sports law? - Kmieciak, Błażej (Biospołeczne uwarunkowania uczestnictwa w kulturze fizycznej i zdrowotnej osób w różnym wieku, 2017)
From time to time the public is informed about the start of the sporting struggles. Championship, Olympics, qualifications and eliminations are events that have become part of individual media centers programs. For many years, during such events there is a discussion about doping. It is widely criticized as an example of violation of fair play principle, which has been present for many generations in sport. This subject was completed in recent years on discussions related to the application of gene doping. There is currently no verified information indicating that any of the countries apply similar techniques to assist athletes. Whether similar action would be unethical? Does gene doping violate the principles of fair play? Did the law define the term of gene doping? In the proposed speech there will be taken reflection on these topics. It will be carried out by the use of appearing during a sports event media materials relating to the abovementioned issues. It will be also assisted by fiction literature, raising in recent years the topic of gene doping.